Manual de gestión de ruido para la mitigación acústica en la central termoeléctrica Celso Castellanos; ubicada en el cantón Lago Agrio, provincia de Sucumbíos - Ordoñez Vélez, Jessica Alexandra (2015)
The objective of this research was to establish the basic of the Central Thermoelectric Celso Castellanos line, therefore a survey was applied to 20 workers of the Central Thermoelectric Celso Castellanos, among other results, it showed that 95% of respondents recorded negative medical history in health in respect of noise pollution. Based on the results of the survey. Determining noise levels generated by the Central Thermoelectric Celso Castellanos, which is located in Canton Lago Agrio, Sucumbíos Province, it went through a sound level meter mark Sound Pro, having established 27 benchmarks within the organization under study, 16 measurements each, which results among others reveals that in points 3,6,17,20,21,22,23 and 25 on the noise level exceeds 80 dB (A) were taken ; in points 11, 24 and 26 to 85 dB (A); and, in point 12 it is 94 dB (A); above 70 dB established by the World Health Organization as maximum noise limits, thereby confirming the existence of the noise values; Define Management Manual for acoustic noise mitigation in Central Thermoelectric Celso Castellanos, which includes the interest and expectations of those involved, and aims to solve the problem that prompted the investigation.